2020
DOI: 10.1002/aorn.13046
|View full text |Cite
|
Sign up to set email alerts
|

Using Virtual Human Technology in Perioperative Team Training Simulations

Abstract: Incorporating virtual human (VH) technology into simulation programs for perioperative education and training can improve interdisciplinary teamwork and communication. The development of VHs allowed interdisciplinary teams at the University of Florida Health Shands Hospital to overcome obstacles during training, such as communication gaps. A multidisciplinary team that included perioperative leaders and quality specialists developed three scenarios for interdisciplinary training to provide participants with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Although technical skills are fundamental to the role of a scrub nurse, the ability to promote safe practice through critical thinking and decision‐making is equally important. It was likely that the immediate feedback provided during the virtual‐reality simulation improved their understanding of the workflow 24,25 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although technical skills are fundamental to the role of a scrub nurse, the ability to promote safe practice through critical thinking and decision‐making is equally important. It was likely that the immediate feedback provided during the virtual‐reality simulation improved their understanding of the workflow 24,25 …”
Section: Discussionmentioning
confidence: 99%
“…It was likely that the immediate feedback provided during the virtual-reality simulation improved their understanding of the workflow. 24,25 Evidence has suggested that only 61.3% of nursing students were confident in applying knowledge to safe practice. 26 Therefore, this study sought to understand the level of confidence among nursing students through virtual-reality simulation.…”
Section: Discussionmentioning
confidence: 99%
“…20 Interprofessional simulations also allow all members of the surgical team to partner in a collaborative environment. 21 This education methodology may be effective for emergent event scenarios (eg, cardiac arrest, malignant hyperthermia response).…”
Section: Tools For Competency Educationmentioning
confidence: 99%
“…Cordar et al [11] proposed a simulator that allows anesthesia residents to work with a mixed reality team that represented on large monitor screens. Furthermore, Brunges et al [24] presented a similar mixed reality technology for interdisciplinary teams. Their results indicated that ineffective preoperative team member communication can result in serious patient harm.…”
Section: Related Workmentioning
confidence: 99%